ANALISIS YURIDIS, ONTOLOGIS, DAN REKONSTRUKSI PERLINDUNGAN HUKUM DALAM SISTEM PERBANKAN NASIONAL (Kajian Hukum Perbankan Syariah dalam Perspektif Kepastian Hukum dan Keadilan Substantif) - Ani Wahyuni; Hasnah Aziz; Ahmad Fahrul Rozi; Oky Rona Wijaya; Regina Yura Fitriah Sari (CV. Lafadz Jaya, 2026)
The existence of Islamic banking in Indonesia constitutes a juridical, philosophical, and sociological necessity within the national legal system. The rapid development of Islamic financial institutions demands legal certainty, especially concerning the implementation of sharia principles in banking agreements and customer protection mechanisms. This study aims to analyze the ontological and juridical position of sharia principles within the Indonesian banking system, examine the legal problems in the implementation of Islamic banking contracts in relation to the principle of freedom of contract under the Civil Code, and reconstruct legal protection mechanisms for Islamic banking customers in both litigation and non-litigation dispute settlement. This research employs normative legal research with statutory, conceptual, philosophical, and case approaches. The legal materials consist of primary, secondary, and tertiary legal sources analyzed using descriptive qualitative methods. The findings reveal that sharia principles have transformed from religious norms into imperative positive law (dwingend recht) through Law Number 21 of 2008 concerning Islamic Banking. Nevertheless, the implementation of sharia contracts still encounters normative conflicts between the principle of freedom of contract and sharia restrictions such as the prohibition of riba, gharar, and maysir. In practice, standard contracts frequently create bargaining inequality between banks and customers. Furthermore, dispute resolution mechanisms remain fragmented due to the dualism between civil procedural law and sharia economic law. The reconstruction of legal protection requires harmonization between national procedural law and Islamic economic law, strengthening mediation institutions and non-litigation settlement mechanisms, and codifying Islamic economic law into statutory legislation to guarantee legal certainty, justice, and consumer protection in the national Islamic banking system.